2012
DOI: 10.1155/2012/739094
|View full text |Cite
|
Sign up to set email alerts
|

Periocular Myxoma in a Child

Abstract: Myxomas are locally invasive, benign mesenchymal neoplasms with odontogenic, osteogenic, or soft tissue origin. Facial myxomas probably account for less than 0.5% of all paranasal sinus and nasal tumors. We report a case of a left painless periocular mass in a 11-month-old girl. The lesion was resected with a clinical diagnosis of lacrimal sac tumor. Histopathology and immunohistochemistry proved the tumor to be a myxoma. There has been no recurrence after 4 years of followup. Midfacial myxomas should be diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…Immunohistochemistry may not be a particularly helpful diagnostic adjunct when evaluating SNM. This is reflected in the case reports and series of infantile SNM since 2000, which all describe positivity for vimentin and negative staining for S100, cytokeratins, BCL2, Alk-1, other neural and muscle markers [9,10,12,22,23,25,26,[28][29][30][31]33]. SMA reactivity, when reported, was focal and weak to negative in SNM [10,23,25,[28][29][30][31], as well in our described case.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Immunohistochemistry may not be a particularly helpful diagnostic adjunct when evaluating SNM. This is reflected in the case reports and series of infantile SNM since 2000, which all describe positivity for vimentin and negative staining for S100, cytokeratins, BCL2, Alk-1, other neural and muscle markers [9,10,12,22,23,25,26,[28][29][30][31]33]. SMA reactivity, when reported, was focal and weak to negative in SNM [10,23,25,[28][29][30][31], as well in our described case.…”
Section: Discussionsupporting
confidence: 76%
“…This is reflected in the case reports and series of infantile SNM since 2000, which all describe positivity for vimentin and negative staining for S100, cytokeratins, BCL2, Alk-1, other neural and muscle markers [9,10,12,22,23,25,26,[28][29][30][31]33]. SMA reactivity, when reported, was focal and weak to negative in SNM [10,23,25,[28][29][30][31], as well in our described case. Two studies have shown that most, but not all, odontogenic myxomas show reactivity for alpha-smooth muscle actin [35,36].…”
Section: Discussionsupporting
confidence: 76%